Posterolateral Sulcus Approach for Spinal Intramedullary Tumor of Lateral Location: Technical Note - Takami, Toshihiro (Neurol Med Chir (Tokyo), 2013)
Posterolateral sulcus (PLS) approach of the spinal cord, being equivalent to the dorsal root entry zone myelotomy, may offer the satisfactory exposure of the spinal intramedullary tumor if applied appropriately. Eight consecutive patients with spinal intramedullary tumors of lateral location underwent the surgery of PLS approach in our institute. There were 6 male and 2 female patients, ranging in age from 34 to 72 years (mean, 57 years). PLS approach was indicated for the intramedullary tumor situated laterally in the spinal cord and that do not contact the posterior or lateral surfaces on magnetic resonance (MR) images before surgery. Total removal of the tumor was achieved in 6 cases except of 2 cases of anaplastic astrocytoma. All 6 patients with total removal of the tumor demonstrated the modest or mild deterioration of motor function on the approach side early after surgery, which resolved within 1 month after surgery. Average grade of the modified McCormick functional schema was 3.5 before surgery and improved to 3.0 at 3 months after surgery. These 6 patients demonstrated satisfactory pain relief early after surgery. Average grade of the sensory pain scale was 2.7 before surgery and improved to 1.7 at 3 months after surgery. PLS approach can be one of the surgical choices to the spinal intramedullary tumors, if applied appropriately. Better indication for PLS approach may be the tumors of the uneven location within the spinal cord associated with moderate or severe local pain.